Soil Application of Tannery Land Plaster: Effects on Nitrogen Mineralization and Soil Biochemical Properties - Caterina Giacometti; Luciano Cavani; Paola Gioacchini; Claudio Ciavatta; Claudio Marzadori (Applied and Environmental Soil Science)
Tannery land plaster (TLP) is a byproduct of lime hydrolysis of leather shavings. Its use in agriculture (organic C ≈ 17%, N ≈ 6% dm) could represent an alternative to landfill or incineration, but the high Cr(III) content (≈5% dm) makes it necessary to evaluate the effect on soil biochemical properties. TLP was therefore added at the rates of 220 and 440 kg of N ha−1 to 2 agricultural soils and incubated for 56 days under controlled conditions. Extractable NH4 +-N and NO3 −-N, CO2-C evolution, microbial biomass-N, protease activity, and extractable Cr were monitored. The organic N was readily mineralized (>50% in the first week) and a significant increase in microbial activity was measured, regardless of soil type and addition rate. Extractable Cr(III) quickly decreased during the incubation. The absence of a negative impact on soil biochemical properties seems to support the use of TLP in agriculture, although further investigations in long-term field experiments are suggested.